Presence of internet marketing and its influence of business success of companies in Bosnia and Herzegovina - Ahmet Sinanagić; Beriz Čivić; Alma Muratović (Economic Review: Journal of Economics and Business, 2019)
The paper briefly highlights the importance of the internet for business operations of modern companies and the possibilities for its inte-gration with traditional marketing activities. The research problem reported in the paper is the identification of presence of internet marketing and its influence on business success of companies in Bosnia and Herzegovina (BiH). The application of the internet in marketing in BiH has still been insufficiently studied. Hence, the research may be more significant as it can serve as a motive for further research in this field. The research aims presented in the paper are the following: 1) to establish whether mar-keting strategies in companies in BiH include the application of the internet in their prepa-ration and realization; 2) to identify the most frequent purposes for which companies in BiH use the internet; 3) to establish the level of integration of the internet and traditional mar-keting activities in companies in BiH; 4) to examine whether the level of integration of the internet and traditional marketing activities affects companies' business success. The resea-rch results showed that the companies with a high level of integration of the internet and traditional marketing activities have on avera-ge better indicators of business success..
Keywords: M31; L86; M39; 330; internet marketing; marketing strategy; business success